Isolated congenital fusion of the gums - Chiabi A; Tchokoteu P; Andze G; Boubakary S; Fouapon V; Minkande Ze J; Gonsu J (Wolters Kluwer Medknow Publications, 2008)
Isolated congenital fusion of the gums is a rare anomaly. Early surgical treatment is indicated, as longstanding cases will impair normal feeding leading to nutritional and growth problems. We report the first case in the Yaoundι Gynaeco-Obstetric and Paediatric Hospital, which was successfully managed surgically.